PENGUATAN KEMANDIRIAN MASYARAKAT MELALUI TRANSFORMASI DIGITAL DAN INOVASI FILTRASI AIR DI KAMPUNG YAMTA - Hotnida Nainggolan; Thelly Sula Hendrina Sembor; Yulius Palumpun; Usman Tahir (Universitas Negeri Makassar, 2026)
Reliance on conventional infrastructure and low digital literacy in border regions often hinder village self-reliance. This community service initiative aims to empower the community of Kampung Yamta PIR II through the digital optimization of village assets and water filtration innovations. The method applied is Asset-Based Community Development (ABCD), which involves the active participation of residents at every stage. Key outcomes of the initiative include: (1) Transformation of data governance through a Digital Village managed independently by village operators; (2) Enhancement of the community’s technical capacity to perform simple water filtration based on local wisdom and carried out through self-reliance to address the crisis of safe drinking water; and (3) Strengthening of spatial identity through participatory mapping. This program involves all village officials and youth leaders, and creates sustainable impacts in the management of local resources. In conclusion, empowerment based on technology transfer and digital literacy significantly enhances community resilience in addressing infrastructure challenges at the village level.